Experimental research of biogas yield and quality produced from chicken manure - Kolodynskij, Vitalij; Baltrėnas, Pranas (International Conference “Environmental Engineering”, 2017)
Biogas is a fuel, which can be produced from a renewable energy source – biomass. Such a gas can be freely used in small farms or food industry to produce heat or electricity. Two main components of biogas – metahne CH4 and carbon dioxide CO2. In some case, if biomass has a big amount of proteins, there can be an aggressive to different constructions gas – hydrogen sulphide H2S in biogas composition. Also, there can be other gases, such as ammonia or hydrogen, but their concentrations are very low. Nowadays it’s extremely important to find a biomass with high energy potential not only to produce “green” energy, but to save the environment from gaseous emissions (greenhouse gases) and soil pollution. The aim of this study – to examine biogas yield and quality, which was produced from chicken manure biomass. To implement research, a small ized bioreactor of periodic operation (total volume – 30 l, operating volume – 20 l) was used. One of the important parameters of biomass is total quality of volatile solids (VS) and quantity of organic matter in one liter of biomass (organic load – VS/l). In this research, there were examined two chicken manure biomasses with different VS and VS/l. The first one reached relatively 3188 g and 160 g/l. The second’s biomass volatile solids quantity reached 1993 g and organic load was 100 g/l. Both biomasses were of the same type and organic matter (chicken manure with 39.85 % concentration of organic matter). During the experimental research, the temperature of anaerobic digestion was mesophilic (35–37 oC). The operation of bioreactor was periodic, this means, that the biomass was held in anaerobic condition till the complete degasation without any partial refill. The total experiment duration reached 66 days. It was found, that the maximum CH4 concentration reached 72.2% (biomass with organic load 100 g/l). To compare biogas yield from biomasses with different organic loading, it must be recalculated to an amount of biogas produced per day from 1 kg of volatile solids (l/d/kg VS). By implementing gained data analysis, it was discovered, that the maximum biogas yield is 7.8 l/d/kg VS (biomass with organic load 100 g/l). According to this research, it will be possible to create and use a smallized bioreactor with chicken manure biomass in small farms to reduce pollution and generate energy.
Keywords: biogas production; biodegradable waste; climate change; energy